Anais Estendidos Do XXI Simpósio Brasileiro De Jogos E Entretenimento Digital (SBGames Estendido 2022) 2022
DOI: 10.5753/sbgames_estendido.2022.226162
|View full text |Cite
|
Sign up to set email alerts
|

Otome Games: mapeamento e análise exploratórios do perfil dos jogadores brasileiros

Abstract: Na década de 2010 fora observado o fenômeno de popularização de jogos conhecidos como Otome Games no ocidente e no Brasil, gênero este voltado para público feminino, sendo geralmente em formato de visual novels ou dating sim. Este estudo realizou um mapeamento e análise exploratórios do perfil dos praticantes brasileiros deste tipo de jogo através de uma revisão narrativa da literatura e de um survey eletrônico, conceitualizando os Otome Games em si e dentro do fenômeno de globalização da cultura pop japonesa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…However, deeper research revealed a vacuum of structured data on the profile and size of the public for this type of game and content in Brazil. Therefore, this work in question aims to be a first structured contribution to the geographic reality in question, which is based on a preliminary publication, duly revised, and expanded, presented at the XXI Brazilian Symposium of Games and Digital Entertainment (Diniz et al 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…However, deeper research revealed a vacuum of structured data on the profile and size of the public for this type of game and content in Brazil. Therefore, this work in question aims to be a first structured contribution to the geographic reality in question, which is based on a preliminary publication, duly revised, and expanded, presented at the XXI Brazilian Symposium of Games and Digital Entertainment (Diniz et al 2022b).…”
Section: Introductionmentioning
confidence: 99%